The Functional Role of Amyloid Precursor Protein at Mitochondria. (20th December 2022) - Strope, Taylor A.; Troutwine, Benjamin R; Lysaker, Colton R; Wilkins, Heather M
Abstract: Background: Aβ is generated from amyloid precursor protein (APP) via sequential proteolytic processing. While APP processing and its localization are well understood, the functional role of APP is largely unknown. APP is expressed almost ubiquitously but is concentrated in neuronal synapses and localizes to mitochondria. The functional consequence of mitochondrial APP localization is not well understood. We leveraged a mutant APP construct which does not localize to mitochondria to interrogate the functional role of APP at mitochondria. Methods: We used a mutant form of APP (3M APP) which harbors mutations at amino acids +41, +44, and +52 (His to Asp). SH‐SY5Y cells were transfected for 24‐48 hours with either WT or 3M APP plasmids. Following transfection, mitochondrial function was analyzed using Seahorse Technology or Vmax spectrophotometric assays of electron transport chain (ETC) function. Mitophagy was examined by qPCR against mitochondrial DNA content. A co‐localization assay using an adenovirus expressing EGFP‐Cox8 was used as a separate measure of mitophagy. To activate mitophagy, cells were either treated with deferiprone (DFP), starvation (glucose and amino acid deprivation), or PINK1 was overexpression. Mitochondrial biogenesis and turnover were measured using an adenoviral vector (MitoTimer). We further assessed the ability of APP to interact with known mitophagy proteins using immunoprecipitation. Results: Compared to WT APP, cells expressing 3M APP showed a decrease in mitochondrial localization as expected. 3M APP led to a significant decrease in complex II and IV flux of the ETC with decreased in complex IV Vmax. 3M APP showed significantly lower mitochondrial mass and biogenesis. Finally, 3M APP expressing cells appeared to have reduced mitophagy when compared to WT APP. We further found that APP interacts with PINK1 and p62 under conditions of enhanced mitophagy. Conclusions: APP localization to mitochondria alters ETC function, mitochondrial mass, and mitophagy. Further studies are in progress to elucidate the mechanisms of APP localization at mitochondria, bioenergetic changes, and mitophagy.